Management Ocular Syphilis in Human Immunodeficiency Virus (HIV) Patients - Alexander Theodore Samosir; N. K. Niti Susila; I Gutsi Ayu Made Juliari; Ida Ayu Ary Paramita; I Made Agus Kusumadjaja (Majalah Oftalmologi Indonesia, 2022)
Introduction: Ocular syphilis is a rare manifestation of syphilis. Ocular syphilis manifestations vary and can occur at all stages of the disease. Syphilis can affect all eye structures, the main complaint is blurred vision, accompanied by non-specific symptoms such as pain in the eye, and does not respond to steroids. Case: The male patient, 54 years old, presents with complaints of both eyes slowly getting worse with a history of sexual multi-partners. Visual acuity in both eyes were light perception bad projection, ophthalmological examination showed cloudy lens, cloudy vitreous, cell (+) flare (+) right eye optic nerve, hyperemia, and left eye optic nerve, pale at temporal. VDRL results: reactive> 1: 512 and TPHA: reactive> 1: 5120. The patient was diagnosed with late latent syphilis and neurosyphilis observation from the Dermatology and Venereology Department and received benzathine penicillin injection therapy. From the Neurology Department the patient was diagnosed with neuro-syphilis and was consulted to VCT department with pre-HAART Stage IV HIV infection (WHO). After receiving penicillin therapy and topical steroids, the patient was experienced improvement in visual acuity. Conclusion: In HIV patients without antiretroviral therapy, Treponema pallidum infection is more common and has manifestations such as ocular syphilis and neurosyphilis. Treatment of ocular syphilis using topical steroids to reduce inflammation and penicillin as the main antibiotic.